A large anterior mediastinal mass in a young infant. (4th February 2022) - Davidson, H; Veerappan, S
Abstract: Funding Acknowledgements: Type of funding sources: None. TITLE: A large anterior mediastinal mass in a young infant Case Report: A 4 week old male neonate, KS was referred to the emergency department with a 24 hour history of increased work of breathing, two brief episodes of apnoeas and inspiratory stridor. There was no infective symptoms or changes to his usual feeding pattern. There was no significant past medical history and he was on no regular medications. A chest x-ray demonstrated a large mediastinal mass and suspicion of cardiomegaly. A transthoracic echocardiogram demonstrated a structurally and functionally normal heart. However, there was a large anterior homogenous soft tissue mass extending to the left ventricular apex which was separate from the pericardium. This mass did not cause any heart chamber compression or compromise. Further cross-sectional imaging with cardiac computed tomography (CT) showed a non-enhancing uniform soft tissue mass occupying the superior and anterior mediastinum without evidence of calcification or fatty components. The lesion was seen to be extending from the root of the neck down to the left cardiac apex region with the total dimensions of the mass being 5.2 x 3.5 x 5cm. There was no compression of the great arteries or the airway. Parasternal ultrasound of the chest showed a starry sky appearance compatible with normal thymic tissue. Overall, the appearances were felt to be compatible with a prominent normal thymus. Discussion: The differential diagnosis of an anterior mediastinal mass in young infants includes germ cell tumours (mainly teratomas), congenital thymic cysts and true thymic hyperplasia(1). These can be difficult to distinguish from the normal large neonatal thymus. The normal thymus can take on a variety of shapes and sizes and still be considered normal. One of the most important features of a normal thymus is the lack of mass effect or compression on the airway or vascular structures(2). True thymic hyperplasia is characterised by an increase in the size and shape of the thymus while preserving thymic architecture. If the anterior mass has a bipyramidal morphology with the presence of gross intercalated fat on CT, these findings are pathognomonic for thymic hyperplasia(3). Thymomas are rare in children and appear as well-defined, rounded or lobulated soft tissue density mass with mild enhancement on CT. It can demonstrate irregular borders with extension into adjacent structures and approximately 30% will have necrosis and internal cystic foci(4). The most common germ cell tumour in the mediastinum is a teratoma with the hallmark being fat, fluid and calcified components on CT(2). Lymphomas are the most common anterior mediastinal mass in children but are usually seen in children older than 5 years. They often cause mass effect with displacement of the trachea. CT scan demonstrates larger nodal areas with hypodense and cystic areas suggestive of necrosis(1).